Learning to ski with Mr. Magee - Van Dusen, Chris (San Francisco : Chronicle Books, 2010)
An encounter with a moose while they are learning to ski provides Mr. Magee and his dog with some unexpected excitement.
Keywords: Stories in rhyme; Skis and skiing -- Juvenile fiction; Dogs -- Juvenile fiction